2008
DOI: 10.1186/1471-2199-9-77
|View full text |Cite
|
Sign up to set email alerts
|

Phi29 polymerase based random amplification of viral RNA as an alternative to random RT-PCR

Abstract: Background: Phi29 polymerase based amplification methods provides amplified DNA with minimal changes in sequence and relative abundance for many biomedical applications. RNA virus detection using microarrays, however, can present a challenge because phi29 DNA polymerase cannot amplify RNA nor small cDNA fragments (<2000 bases) obtained by reverse transcription of certain viral RNA genomes. Therefore, ligation of cDNA fragments is necessary prior phi29 polymerase based amplification. We adapted the QuantiTect W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 16 publications
0
63
0
Order By: Relevance
“…RNA extraction from biological samples was processed with TRI Reagent (Molecular Research Center) according to the manufacturer's recommendations. After extraction, viral RNAs were reverse transcribed and then amplified using the whole-transcriptome amplification (WTA) protocol (QuantiTect Whole Transcriptome kit; Qiagen) as described previously (3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA extraction from biological samples was processed with TRI Reagent (Molecular Research Center) according to the manufacturer's recommendations. After extraction, viral RNAs were reverse transcribed and then amplified using the whole-transcriptome amplification (WTA) protocol (QuantiTect Whole Transcriptome kit; Qiagen) as described previously (3).…”
Section: Methodsmentioning
confidence: 99%
“…The amplification step, which is more often limiting for this technology, has also benefited from recent developments. Phi29 polymerase-based amplification methods provide amplified DNA with minimal changes in sequence and relative abundance for many biomedical applications (3,31,40). The amplification factor varied from 10 6 to 10 9 , and it was also demonstrated that coamplification occurred when viral RNA was mixed with bacterial DNA (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Circular targets are ideal for this amplification strategy. However, linear targets can also be amplified in a similar manner (Dean et al 2001;Berthet et al 2008). For short linear DNA viruses and cDNA, amplification is less efficient, and additional steps, such as ligation, may have to be included for amplification (Berthet et al 2008).…”
Section: Displacement Amplificationmentioning
confidence: 99%
“…However, linear targets can also be amplified in a similar manner (Dean et al 2001;Berthet et al 2008). For short linear DNA viruses and cDNA, amplification is less efficient, and additional steps, such as ligation, may have to be included for amplification (Berthet et al 2008). This strategy has also been successful in studying different viral metagenomes, and several novel viruses have been discovered by this method, such as a fibropapilloma virus in sea turtles (Ng et al 2009), Anellovirus in harbor seals (Ng et al 2011), Bocavirus in pigs (Blomstro¨m et al 2009), and Papillomaviruses in humans (Rector et al 2004).…”
Section: Displacement Amplificationmentioning
confidence: 99%